Vitiligo-like lesions induced by cyclin-dependent kinase 4/6 inhibitor Palbociclib: a case report and literature review - Shan Gao; Guanjing Wei; Yanrong Hao (Frontiers Media S.A., 2023)
Endocrine therapy has played an essential role in hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) breast cancer. With the continuous development of endocrine targeting drugs, especially the emergence of selective cyclin-dependent kinase (CDK4/6) inhibitors, the overall survival time in patients with HR+HER2− advanced breast cancer has been greatly improved. Their adverse reactions also need more attention in response to the climbing number of CDK4/6 inhibitors. The common side effects of CDK4/6 inhibitors were hematological toxicity, diarrhea, and liver function damage. Skin toxicity related to CDK4/6 inhibitors was rare. We describe herein our preliminary observation of one HR+HER2− advanced metastatic breast cancer patient diagnosed with vitiligo-like lesions after 10 months of taking Palbociclib. Hoping to share our experience to increase the clinician awareness of this unusual adverse and contribute to the information in the literature.